2019
DOI: 10.1038/s41467-019-12064-1
|View full text |Cite
|
Sign up to set email alerts
|

Typhoid toxin exhausts the RPA response to DNA replication stress driving senescence and Salmonella infection

Abstract: Salmonella Typhi activates the host DNA damage response through the typhoid toxin, facilitating typhoid symptoms and chronic infections. Here we reveal a non-canonical DNA damage response, which we call RING (response induced by a genotoxin), characterized by accumulation of phosphorylated histone H2AX (γH2AX) at the nuclear periphery. RING is the result of persistent DNA damage mediated by toxin nuclease activity and is characterized by hyperphosphorylation of RPA, a sensor of single-stranded DNA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 59 publications
1
60
0
Order By: Relevance
“…γH2AX provided consistent, reliable results on isolated myoblasts in vitro following γ‐irradiation and on muscle tissue cross sections (see below). γH2AX is best known as a indicator of DNA damage, and, according to PubMed, γH2AX has been used as an indicator of senescence in nearly 500 manuscripts, including several studies 28,45‐47 that use γH2AX as the sole marker of senescence. However, due to the importance of using multiple markers to quantify senescent cells (reviewed by Ref.…”
Section: Resultsmentioning
confidence: 99%
“…γH2AX provided consistent, reliable results on isolated myoblasts in vitro following γ‐irradiation and on muscle tissue cross sections (see below). γH2AX is best known as a indicator of DNA damage, and, according to PubMed, γH2AX has been used as an indicator of senescence in nearly 500 manuscripts, including several studies 28,45‐47 that use γH2AX as the sole marker of senescence. However, due to the importance of using multiple markers to quantify senescent cells (reviewed by Ref.…”
Section: Resultsmentioning
confidence: 99%
“…While the direct induction of senescence by genotoxins further implicates bacteria in oncogenesis, it is less clear whether senescence is subverted by pathogens to promote infection. One example recently implicated in senescence includes the typhoid toxin [19], which is a unique chrimeric toxin encoded by the serovars of the intracellular pathogen Salmonella that cause enteric fever (e.g., typhoidal serovars S. Typhi, S. Paratyphi) and inflammatory gastroenteritis (e.g., non-typhoidal serovars S. Javiana, S. Montevideo) in humans [101][102][103]. The typhoid toxin has been reported to play important roles during the Salmonella infection of mice and humans including pathogen dissemination and host colonisation, the suppression of inflammatory responses, bacteraemia, typhoid fever and chronic Salmonella carriage [103][104][105][106].…”
Section: Induction Of Senescencementioning
confidence: 99%
“…The typhoid toxin mediates its toxigenic activities through CdtB, which is exocytosed from infected mammalian cells in a chimeric complex with the pertussis toxin subunits PltA and Plt, the latter facilitate toxin endocytosis into bystander cells where CdtB causes DNA damage [102,103,107]. Recent work on the typhoid toxin revealed that senescence is hijacked by S. Typhi and S. Javiana to enhance the intracellular Salmonella infection of macrophage and fibroblast-like cells [19]. A senescent-like phenotype was triggered by two mutually exclusive DDRs in distinct cell populations: ATM-dependent γH2AX foci in G1 or ATR-dependent γH2AX localised at the nuclear periphery in G2/M, referred to as RING (response induced by a bacterial genotoxin).…”
Section: Induction Of Senescencementioning
confidence: 99%
See 1 more Smart Citation
“…One of the consequences of DNA damage in cells exposed in vitro to bacterial genotoxins is 122 the acquisition of senescence (Blazkova et al, 2010;Ibler et al, 2019), which is associated with 123 secretion of a broad panel of mediators, mainly related to a pro-inflammatory effect, such as 124 IL1, IL6, and IL8 (Hernandez-Segura et al, 2018). Induction of the senescent phenotype in in 125 vivo bacterial infection is poorly characterized.…”
mentioning
confidence: 99%